Comparative Analysis of Biochemical Abnormalities in Diabetic Patients with or without Cardiovascular Complications - Akram Yousif, Salman Abbas, Amanullah Bhutto, Muhammad Zubair, Mumtaz Ali Lakho, Muhammad Rahman Khalid (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess the lipid profile and blood glucose concentration association between diabetic patients with and without cardiac disease. Study design: Case-control study Place and Duration: National Institute of Cardiovascular Diseases Karachi from January 2021 to June 2021 Methodology: The study included a total of 180 participants categorized into comparative groups. Diabetic patients were categorized into cardiac and non-cardiac patients. Demographic data were collected using a questionnaire, and clinical data were recorded with the physical examination. Blood was collected from all patients for further glucose and lipid profile testing. Data were evaluated using SPSS version 21. Results: The average age was 49.53 ± 11.24 and 54.38 ± 11.87 years for non-cardiac and cardiac patients. Whereas BMI of 28.16 ± 5.89 and 27.64 ± 4.18 was observed in diabetic patients with non-cardiac and cardiac diseases. A total of 73 (81.2%) were smokers with cardiac diseases, and 58 (64.4%) were smokers without cardiac disease. A total of 80% of cardiac and 57.7% of non-cardiac patients had a family history of diabetes. Significant high levels of Cholesterol, LDL-C, and Glucose were observed. However, significantly lower levels of HDL-C were observed between patients with and without cardiac disease. Conclusion:The results of the current study indicate that patients with diabetes having cardiovascular disease have a significant association with biochemical parameters. Those with diabetes are more likely to acquire hyperlipidemia. Keywords: Biochemical parameter, cardiovascular disease, Diabetes Mellitus, Cholesterol, Dyslipidemia